REKONSTRUKSI PERAN TUAN GURU DALAM PENCEGAHAN DAN PEMBERANTASAN NARKOBA DI LOMBOK - MS Udin; tuti harwati (Islam Futura, 2019)
Research on reconstruction on the role of Tuan Guru (teacher) in the prevention and eradication of drugs in Lombok is field research using a qualitative research approach. This study aims to explore three critical issues. First, it analyzes the role of Tuan Guru in Lombok society. Second, it explains the reconstruction format of Tuan Guru as the efforts of preventing and eradicating drugs. Third, it describes the impact of the reconstruction role of Tuan Guru on drug prevention and eradication efforts. The findings elucidate that first: the roles of Tuan Guru in the Lombok Community were: 1) as an Ulama, 2) as a social problem controller or supervisor, 3) as an innovator of change towards betterness, 4) as a supporter of community independence. Second, the formats of reconstruction roles which were carried out in the efforts of preventing and eradicating drugs were as follows: 1) carry out a personal approach mechanism, 2) enforce a real action, 3) serve a counseling activity, 4) empower the community economy. Third, the roles played by Tuan Guru in preaching to deal with the drug problem were found to be very effective. Tuan Guru had succeeded in eliminating drug effects on the young generation. This could be proven as the number of drug cases decreases as reported by the drug investigation directorate of Lombok Barat.